Integrating security and software engineering advances and future visions - Mouratidis, Haralambos 1977-; Giorgini, Paolo (Gale virtual reference library, 2007)
"This book investigates the integration of security concerns into software engineering practices, drawing expertise from the security and the software engineering community; and discusses future visions and directions for the field of secure software engineering"--Provided by publisher.